Particles Co-orbital to Janus and to Epimetheus: A Firefly Planetary Ring - Winter, Othon C. [UNESP]; Souza, Alexandre P. S. [UNESP]; Sfair, Rafael [UNESP]; Winter, Silvia M. Giuliatti [UNESP]; Mourão, Daniela C. [UNESP]; Foryta, Dietmar W. (American Astronomical Society, 2018)
The Cassini spacecraft found a new and unique ring that shares the trajectory of Janus and Epimetheus, co-orbital satellites of Saturn. Performing image analysis, we found this to be a continuous ring. Its width is between 30% and 50% larger than previously announced. We also verified that the ring behaves like a firefly. It can only be seen from time to time, when Cassini, the ring, and the Sun are arranged in a particular geometric configuration, in very high phase angles. Otherwise, it remains in the dark, invisible to Cassini's cameras. Through numerical simulations, we found a very short lifetime for the ring particles, less than a couple of decades. Consequently, the ring needs to be constantly replenished. Using a model of particle production due to micrometeorites impacts on the surfaces of Janus and Epimetheus, we reproduce the ring, explaining its existence and the firefly behavior.
Keywords: planets and satellites: dynamical evolution and stability; planets and satellites: individual (Epimetheus, Janus); planets and satellites: rings